Interactions between SNPs affecting inflammatory response genes are associated with multiple myeloma disease risk and survival. Issue 11 (2nd November 2017) - Nielsen, Kaspar René; Rodrigo-Domingo, Maria; Steffensen, Rudi; Baech, John; Bergkvist, Kim S; Oosterhof, Liesbeth; Schmitz, Alexander; Bødker, Julie Støve; Johansen, Preben; Vogel, Ulla; Vangsted, Anette; Dybkær, Karen; et al.
Abstract: The origin of multiple myeloma depends on interactions with stromal cells in the course of normal B-cell differentiation and evolution of immunity. The concept of the present study is that genes involved in MM pathogenesis, such as immune response genes, can be identified by screening for single-nucleotide polymorphisms (SNPs) involved in the immune response and a subsequent statistical analysis that focusses on the association of SNPs, certain haplotypes or SNP–SNP interactions with MM risk and prognosis. We genotyped 348 Danish patients and 355 controls for 13 SNPs located in the TNFA, IL-4, IL-6, IL-10 and CHI3L1 gene promoters. The occurrence of single polymorphisms, haplotypes and SNP–SNP interactions were statistically analyzed for association with disease risk and outcome following high-dose therapy. Identified genes that carried SNPs or haplotypes that were identified as risk or prognostic factors were studied for expression in normal B-cell subsets and myeloma plasma cells. We observed a significantly reduced risk when harboring the TNFA- 238A allele (OR = 0.51 (0.29–0.86)) and interactions between the TNFA -1031T/C * and IL-10 -3575T/A ( p = .007) as well as the TNFA -308G/A * and IL-10 -1082G/A ( p = .008) allels. By statistical approaches, we observed association between prognosis and the TNFA -857CC genotype (HR = 2.80 (1.29–6.10)) and IL-10 -1082GG + GA genotypes (HR = 1.93 (1.07–3.49)) and interactions between IL-6 -174G/C and IL-10 -3575T/A ( p = .001) and between TNFA -308G/A and IL-4 -1098T/G ( p = .005). The 'risk genes' were analyzed for expression in normal B-cell subsets ( N = 6) from seven healthy donors and we found TNFA and IL-6 expressed both in naïve and in memory B cells when compared to preBI, II, immature and plasma cells. The 'prognosis genes' CHI3L1, IL-6 and IL-10 were differential expressed in malignant plasma cells when comparing poor and good prognosis groups based on to the TC classification. In summary, these findings suggest that TNFA, IL-4, IL-6, IL-10 and CHI3L1 might be important players in MM pathogenesis during disease initiation and drug resistance in multiple myeloma.